VIGOTSKY’S SOCIOCULTURAL: AN ANALYTICAL STUDY IN ARABIC LANGUAGE LEARNING - Mustafiqul Hilmi; Ayu Miranda (Kitaba, 2025)
Sociocultural theory, initially proposed by Vygotsky, provides a framework for understanding human cognitive development and mental functions. At its core, sociocultural theory posits that learning and cognitive development—including language acquisition—occur through social interactions. This study aims to explore how second language acquisition can be explained through the sociocultural perspective, specifically examining how second language learners acquire language through collaboration and interaction with other speakers. The research employs a qualitative literature review method, drawing data from various sources such as books and scholarly articles relevant to the study’s objectives. The findings indicate that Vygotsky’s sociocultural theory is applicable to learning Arabic as a second language. Key concepts from Vygotsky’s theory, such as the Zone of Proximal Development (ZPD), scaffolding through adult mediation, micro genesis, inner speech, private speech, and activity theory, offer valuable perspectives for developing Arabic language skills. These insights underscore the importance of social interaction in fostering language learning and suggest practical implications for teaching practices.